ANALISIS PRODUKTIVITAS PADI DAN PERUBAHAN LUAS LAHAN PERTANIAN AKIBAT ALIH FUNGSI LAHAN DI KECAMATAN NGEMPLAK KABUPATEN BOYOLALI - Zuhdiyah Matienatul Iemaaniah; Setyaning Pawestri (Fakultas Pertanian, Universitas Janabadra, 2024)
Ngemplak District is one of the sub-districts in Boyolali Regency and directly borders Surakarta City, which is the economic center of the Soloraya Region. This sub-district is dominated by rice farming which is almost cultivated in various villages. More than 90% of rice farming land is cultivated by the population. From year to year, agricultural land is increasingly experiencing a decrease in land area due to land conversion. Built-up land is expanding in inverse proportion to the area of rice farming land. This research activity aims to analyze the relationship between rice productivity and the condition of agricultural land in Ngemplak District. This research was analyzed using Pearson product moment correlation which was supported by spatial analysis with proof of image maps and map results of built and undeveloped land cover. The land cover map is overlaid from the 2009 land cover map to existing conditions and the results of surveys conducted by the research team. The results of this research show that there is no correlation between changes in land use and rice productivity results in Ngemplak District although there were decreasing in agricultural land recently in 10 years widely 177 hectares. Key-words: food security; landuse change; paddyINTISARI Kecamatan Ngemplak merupakan salah satu kecamatan yang berada di Kabupaten Boyolali dan berbatasan langsung dengan Kota Surakarta yang merupakan pusat perekonomian di Kawasan Soloraya. Kecamatan ini didominasi dengan pertanian padi yang hampir dibudidayakan di berbagai desa. Lahan pertanian padi lebih dari 90% dibudidayakan oleh penduduknya. Lahan pertanian dari tahun ke tahun semakin mengalami penurunan luas lahan yang disebabkan oleh alih fungsi lahan. Lahan terbangun semakin meluas berbanding terbalik dengan luas lahan pertanian padi. Penelitian ini bertujuan untuk menganalisis hubungan produktivitas padi dengan luas lahan pertanian yang ada di Kecamatan Ngemplak. Penelitian ini dianalisis dengan korelasi pearson product moment yang didukung dengan analisis spasial dengan pembuktian peta citra dan hasil peta tutupan lahan terbangun dan tidak terbangun. Peta tutupan lahan dioverlay dari peta tutupan lahan tahun 2009 hingga kondisi eksisting serta hasil survey yang dilakukan tim peneliti. Hasil penelitian ini menunjukkan bahwa tidak terdapat korelasi antara perubahan penggunaan lahan dan produktivitas padi di Kecamatan Ngemplak meskipun lahan pertanian mengalami penurunan luas 177 hektar dalam 10 tahun terakhir. Kata kunci: alihfungsi lahan; ketahanan pangan; padi